The Antidepressant Effects of (Arcangelisia flava (l.) Merr) Water-Soluble Extract in Balb-C Mice Reviewed from Immobility Time by Forced - A, Tiara; H, Arief R; Sudarsono, Sudarsono (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2014)
This study was conducted to examine / determine the antidepressant effects of (Arcangelisiaflava L.) onÃ‚Â immobility timeÃ‚Â of the white male mice strain Balb-c by the forced swim testÃ‚Â method.Ã‚Â The method of research using laboratory animals such as 25 micewas divided into 5 groups.Ã‚Â As a negative control group was only given distilled waterÃ‚Â ad libitum.Ã‚Â Amitryptiline was used as the positive control group; the experiment group was a water-soluble extract of A.flava by Ã‚Â multiple doses.Ã‚Â The results showed that theÃ‚Â best antidepressant effects were312 mg/kgBW ; it had a minimum ofÃ‚Â immobility timeÃ‚Â compared with the other groups.